The pricing behaviour of firms in the euro area: new survey evidence - Silvia Fabiani; Martine Druant; Ignacio Hernando; Claudia Kwapil; Bettina Landau; Claire Loupias; Fernando Martins; Thomas Y. Mathä; Roberto Sabbatini; Harald Stahl; Ad C.J. Stokman (European Central Bank (ECB), 2005)
This study investigates the pricing behaviour of firms in the euro area on the basis of surveys conducted by nine Eurosystem national central banks, covering more than 11,000 firms. The results, robust across countries, show that firms operate in monopolistically competitive markets, where prices are mostly set following markup rules and where price discrimination is common. Around one-third of firms follow mainly time-dependent pricing rules while twothirds allow for elements of state-dependence. The majority of firms take into account past and expected economic developments in their pricing decisions. Price stickiness is mainly driven by customer relationships – explicit and implicit contracts – and coordination failure. Firms adjust prices asymmetrically in response to shocks: while cost shocks have a greater impact when prices have to be raised than when they have to be reduced, reductions in demand are more likely to induce a price change than increases in demand.
Keywords: E30; D40; 330; Inflation persistence; nominal rigidity; price setting; real rigidity; survey data; Preismanagement; Marktstruktur; Eurozone; EU-Staaten